Component of Caramel Food Coloring, THI, Causes Lymphopenia Indirectly via a Key Metabolic Intermediate. Issue 5 (19th May 2016) - Ohtoyo, Mamoru; Machinaga, Nobuo; Inoue, Ryotaku; Hagihara, Katsunobu; Yuita, Hiroshi; Tamura, Masakazu; Hashimoto, Ryuji; Chiba, Jun; Muro, Fumihito; Watanabe, Jun; Kobayashi, Yoshimasa; Abe, Koji; et al.
Summary: Caramel color is widely used in the food industry, and its many variations are generally considered to be safe. It has been known for a long time that THI (2-acetyl-4-(tetrahydroxybutyl)imidazole), a component of caramel color III, causes lymphopenia in animals through sphingosine 1-phosphate (S1P) lyase (S1PL) inhibition. However, this mechanism of action has not been fully validated because THI does not inhibit S1PL in vitro. To reconcile this situation, we examined molecular details of THI mechanism of action using "smaller" THI derivatives. We identified a bioactive derivative, A6770, which has the same lymphopenic effect as THI via S1PL inhibition. In the case of A6770 we observe this effect both in vitro and in vivo, and demonstrate that A6770 is phosphorylated and inhibits S1PL in the same way as 4-deoxypyridoxine. In addition, A6770 was detected in rat plasma following oral administration of THI, suggesting that A6770 is a key metabolic intermediate of THI. Graphical Abstract: Highlights: Synthesis and characterization of THI derivatives led to the discovery of A6770 A6770 has a lymphopenic effect via S1P lyase inhibition A6770 is phosphorylated and the phosphorylated form directly inhibits S1P lyase A6770 is detected in plasma following oral administration of THI to animals Abstract : Ohtoyo et al. identified A6770 as a novel S1P lyase inhibitor. Mechanistic studies revealed that A6770 is phosphorylated and then directly inhibits S1P lyase. Also, A6770 was detected following oral administration of THI to animals. These results provide a convincing theory about the mechanism of action of THI.